The Nature and Prevalence of Pain in Dreams - Antonio L Zadra; Tore A Nielsen; Anne Germain; Gilles Lavigne; DC Donderi (Pain Research and Management)
BACKGROUND: Little is known about the frequency and nature of pain in dreams. Several authors have suggested that pain may be beyond the representational capability of dreaming.